Effect of local cooling on excitation-contraction coupling in myasthenic muscle: Another mechanism of ice-pack test in myasthenia gravis. Issue 11 (November 2017) - Yamamoto, Daisuke; Imai, Tomihiro; Tsuda, Emiko; Hozuki, Takayoshi; Yamauchi, Rika; Hisahara, Shin; Kawamata, Jun; Shimohama, Shun
Highlights: We evaluated the effects of local cooling on muscle twitch in myasthenia gravis. Local cooling induced amelioration of impaired excitation-contraction coupling in ice-pack-positive myasthenia gravis. The ice-pack test induces effects on synaptic transmission and excitation-contraction coupling. Abstract: Objective: The ice-pack test is a convenient diagnostic testing procedure for myasthenia gravis (MG). We investigated the underlying mechanism of the ice-pack test performed on bilateral masseters. Methods: We performed trigeminal repetitive nerve stimulation (RNS), excitation-contraction (E-C) coupling assessment (Imai's method) and bite force measurement before and after cooling of the masseters in MG patients and normal controls. After placing the ice-pack on the masseters for 3 min, serial recordings of the three tests were performed at various time intervals during 10 min after cooling. Results: The bite force increased significantly after cooling in ice-pack-positive MG patients. The acceleration and acceleration ratio (acceleration at a given time to baseline acceleration) of jaw movement increased significantly after cooling of the masseters in ice-pack-positive MG patients compared to ice-pack-negative patients and normal controls. The prolonged effect of cooling continued until the end of recording even though decremental response to RNS had returned to baseline value. Conclusions: Cooling of myasthenic muscle may induce two effects. One is relatively short effect on electrical synaptic transmission at the endplate, and another is prolonged effect on E-C coupling in the muscle. Significance: The ice-pack test induces a prolonged effect of ameliorating impaired E-C coupling in MG.